Water and nitrogen input optimization for jujube trees under surge root irrigation based on weighted grey correlation model - Dai, Zhiguang; Fei, Liangjun; Zhong, Yun; Huang, Deliang (International Journal of Agricultural and Biological Engineering, 2019)
In order to obtain the optimal input of water and nitrogen (W&N) suitable for the jujube trees in Northern Shaanxi, 12 treatments had been set in the demonstration base of micro-irrigation jujube tree of Mizhi County in 2014-2015 through field experiment of jujube trees under surge root irrigation (SRI), in which three soil moisture levels (high moisture level W1: 60%-85%θ, middle moisture level W2: 50%-75%θ, low moisture level W3: 40%-65%θ) and four nitrogen input levels (high nitrogen F75: 0.75 kg/plant, middle nitrogen F50: 0.50 kg/plant, low nitrogen F25: 0.25 kg/plant, no nitrogen F0: 0.00 kg/plant) were set. Through analyzing the effects of different W&N inputs on the yield, net income (NI) and W&N utilization efficiency (WUE and NUE) of jujube trees and establishing a weighted grey correlation model, the optimization of W&N input for jujube trees could be achieved under SRI. Results showed that different W&N inputs had significant influences on yield, NI, WUE and NUE. Along with the increase of soil moisture content, the yield and NUE increased, while WUE decreased gradually, and the NI had the tendency to increase first and then decrease. Along with the increase of nitrogen input, the yield, NI and WUE had the tendency to increase first and then decrease while the NUE decreased significantly, and the yield, NI, WUE and NUE could not reach the maximum at the same time. Through the study on the grey correlation model of jujube tree’s comprehensive benefit based on the yield, NI, WUE and NUE, results showed the comprehensive benefit of jujube trees was significantly different when W&N input was different, and the gray correlation degree of W2F25 treatment was the highest in two years, which means that the soil moisture content of 50%-75%θ and nitrogen input of 0.25 kg/plant was the optimal W&N input for jujube trees under SRI in Northern Shaanxi area.Keywords: surge root irrigation, input of water and nitrogen, jujube tree, comprehensive benefit, grey correlation modelDOI: 10.25165/j.ijabe.20191203.3541Citation: Dai Z G, Fei L J, Zhong Y, Huang D L. Water and nitrogen input optimization for jujube trees under surge root irrigation based on weighted grey correlation model. Int J Agric & Biol Eng, 2019; 12(3): 45–51.